Simple procedure for the synthesis of gamma-hydroxy-alpha,beta-(E)-alkenoic esters: formal synthesis of (+)-macrosphelides A and B - Rao, K. Srinivasa; Mukkanti, K.; Reddy, D. Srinivasa; Pal, Manojit; Lqbal, Javed (Tetrahedron Letters, 2005)
A highly trans-selective conjugate reduction of 7-hydroxy-alpha,beta-alkynoic esters to produce gamma-hydroxy-alpha,beta-(E)-alkenoic esters using LiAlH4 is reported. The application of this methodology is demonstrated by a formal synthesis of the potent cell-cell adhesion inhibitors (+)-macrosphelides A and B. (c) 2005 Elsevier Ltd. All rights reserved.

Concise asymmetric route to the antibiotic macrolides patulolide A and pyrenophorin - Rao, K. Srinivasa; Reddy, D. Srinivasa; Mukkanti, K.; Pal, Manojit; Iqbal, Javed (Tetrahedron Letters, 2006)
In this letter, we describe an enantiospecific route to patulolide A and pyrenophorin through the synthesis of known protected seco acid precursors starting from commercially available (S)-ethyl lactate. (c) 2006 Elsevier Ltd. All rights reserved.